2016
DOI: 10.1111/jir.12300
|View full text |Cite
|
Sign up to set email alerts
|

Social workers' attributions towards individuals with dual diagnosis of intellectual disability and mental illness

Abstract: The results are discussed in relation to the core values of social work and to professional identity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 50 publications
3
19
0
Order By: Relevance
“…One study did examine stigma towards those with an ID and co‐occurring mental health diagnosis in social workers. They found the stereotype of dangerousness was the strongest predictor of stigmatising behaviours (Araten‐Bergman & Werner ). Although the impact of belonging to multiple stigmatised groups is not well studied, it has been shown that belonging to multiple stigmatised groups can increase the amount of stigma experienced (Burke‐Miller et al .…”
Section: Introductionmentioning
confidence: 99%
“…One study did examine stigma towards those with an ID and co‐occurring mental health diagnosis in social workers. They found the stereotype of dangerousness was the strongest predictor of stigmatising behaviours (Araten‐Bergman & Werner ). Although the impact of belonging to multiple stigmatised groups is not well studied, it has been shown that belonging to multiple stigmatised groups can increase the amount of stigma experienced (Burke‐Miller et al .…”
Section: Introductionmentioning
confidence: 99%
“…To get a better sense of this we must look at the prevailing evidence and allow the empirical data to inform us on these matters. According to Araten-Bergman and Werner [27] there are some elevated risks when it comes to dual-diagnoses. For example, R. Berger DOI: 10.4236/oalib.1104768 4 Open Access Library Journal there appears to be an increased risk of violence when people are dealing with co-existing diagnoses involving intellectual disabilities, psychotic disorders, schizophrenia, bipolar disorder, adjustment disorder, conduct disorder, and substance use disorder [16] [25] [27].…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Araten-Bergman and Werner [27] there are some elevated risks when it comes to dual-diagnoses. For example, R. Berger DOI: 10.4236/oalib.1104768 4 Open Access Library Journal there appears to be an increased risk of violence when people are dealing with co-existing diagnoses involving intellectual disabilities, psychotic disorders, schizophrenia, bipolar disorder, adjustment disorder, conduct disorder, and substance use disorder [16] [25] [27]. Other researchers have found additional clinical disorders to also come with a higher risk of violent behavior, such as with personality disorders (e.g., antisocial and borderline), alcohol addiction, delusional disorder, attention-hyperactivity disorder, and developmental disorders [4] [19] [20].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations